Comparative Transcriptome Analysis Provides Insights Into Yellow Rind Formation and Preliminary Mapping of the Clyr (Yellow Rind) Gene in Watermelon - Liu, Dongming; Yang, Huihui; Yuan, Yuxiang; Zhu, Huayu; Zhang, Minjuan; Wei, Xiaochun; Sun, Dongling; Wang, Xiaojuan; Yang, Shichao; Yang, Luming (Frontiers in Plant Science, 2020)
As an important appearance trait, the rind color of watermelon fruit affects the commodity value and further determines consumption choices. In this study, a comparative transcriptome analysis was conducted to elucidate the genes and pathways involved in the formation of yellow rind fruit in watermelon using a yellow rind inbred line WT4 and a green rind inbred line WM102. A total of 2,362 differentially expressed genes (DEGs) between WT4 and WM102 at three different stages (0, 7, and 14 DAP) were identified and 9,770 DEGs were obtained by comparing the expression level at 7 DAP and 14 DAP with the former stages of WT4. The function enrichment of DEGs revealed a number of pathways and terms in biological processes, cellular components, and molecular functions that were related to plant pigment metabolism, suggesting that there may be a group of common core genes regulating rind color formation. In addition, next-generation sequencing aided bulked-segregant analysis (BSA-seq) of the yellow rind pool and green rind pool selected from an F2 population revealed that the yellow rind gene (clyr) was mapped on the top end of chromosome 4. Based on the BSA-seq analysis result, the yellow rind gene (clyr) was further confined to a region of 91.42 kb by linkage analysis using 1,106 F2 plants. These results will aid in identifying the key genes and pathways associated with yellow rind formation and elucidating the molecular mechanism of rind color formation in watermelon.